Increased mortality in septic shock with the 4G/4G genotype of plasminogen activator inhibitor 1 in patients of white descent - García-Segarra, Gloria; Espinosa, Gerard; Tassies, Dolors; Oriola, Josep; Aibar, Jesús; Bové, Albert; Castro, Pedro; Reverter, Joan-Carles; Nicolás, Josep-Maria (Intensive care medicine, 2007)
To evaluate the effect of the 4G/5G PAI-1 gene polymorphism on the development of organ failure and outcome in critically ill patients with septic syndromes. Prospective, observational study in a medical intensive care unit of a university hospital. 224 consecutively admitted patients. Epidemiological data, severity scores, and the primary site of infection were recorded. DNA genotyping of the PAI-1, TNF-beta, and IL1-ra genes, and measurement of plasma PAI-1 antigen and D-dimer were carried out. The primary outcome variables were organ dysfunction and mortality. Eighty-eight subjects had septic shock at ICU entry or within 48 h from admission. Homozygotes for the 4G allele exhibited higher plasma concentrations of PAI-1 antigen and D-dimer than 4G/5G and 5G/5G subjects). ICU mortality was 44.0% in patients with 4G/4G, 23.4% in 4G/5G and 12.5% in 5G/5G, mainly due to multiorgan failure. After adjusting for SAPS II at admission the genotypes independently associated with ICU mortality in septic shock were TNF-B2/B2 (OR 2.83, 1.04-7.67) and 4G/4G of PAI-1 (OR 2.23, 1.02-4.85). The PAI-1 genotype did not determine susceptibility to infection or the outcome in nonseptic systemic inflammatory response syndrome, sepsis, severe sepsis, and nosocomial septic shock. Homozygosity for 4G of the PAI-1 gene confers an increase in the risk of mortality in adult patients with septic shock due to a greater organ failure.